Consumers' intentions to purchase organic food products - Syaidatina Akila Mohamad Azizan; Norazah Mohd Suki (2017)
The Theory of Planned Behaviour (TPB) is applied as the guiding principle in this conceptual paper with the aims to discuss the factors in influencing consumers' intention to purchase organic food products among Muslim consumers. The literature review exposed that attitude, health concern, environmental concern and labelling affect consumer intention to purchase organic food, and moderated by Islamic values. Results suggest the role of religiousity in firming up the intention to purchase organic food. This paper extends the literature reviews on the consumer behavioural intention towards organic food products by incorporating religiousity values which have been lacking in previous research in sustainable food consumption and also gather another perspective of the role of halal and eco-labelling in influencing consumers' interpretation of the products. Further empirical studies can be carried out to assess the underlying linkages among the factors and uncover the viable model for future research.